Promosi Online Media Sosial Instagram dan Kepuasan Informasi tentang Industri Fashion - Yoselina; Oktavianti, Roswita (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In today's era, with technology that is developing quite rapidly in the field of social media, this has a lot of impact on business people who want to easily disseminate their products to a large audience. The existence of technology has a big influence on the lives of the public. With technology, the life and activities of the audience become very practical and fast. This research was conducted with the aim of knowing whether there was an effect of online promotion on social media Instagram @Carmel_id on the satisfaction of information about the fashion industry among female students and career women. If so, how much influence does online promotion have on social media Instagram @Carmel_id on the satisfaction of information about the fashion industry among female students and career women. This study applies the Uses and Gratification theory with a quantitative approach. The population of this research are college students and career women. The research data collection was carried out by distributing questionnaires to 100 female students and career women @Carmel_id followers. The collected data will be processed through SPSS 26. This study shows that there is an effect of online promotion on information satisfaction by 77.6%, while 22.4% is influenced by other factors. This research shows that if online promotions increase, information satisfaction will also increase. Di era sekarang ini, dengan teknologi yang semakin berkembang cukup pesat di bidang media sosial, dan hal tersebut sangat menimbulkan banyak dampak bagi pebisnis yang ingin menyebarluaskan produknya kepada banyak khalayak dengan mudah. Adanya teknologi menimbulkan pengaruh yang besar pada kehidupan khalayak. Adanya teknologi, kehidupan dan aktivitas khalayak menjadi sangat praktis dan cepat. Penelitian ini dilaksanakan dengan tujuan mengetahui apakah terdapat pengaruh promosi online media sosial Instagram @Carmel_id terhadap kepuasan informasi tentang industri fashion pada mahasiswi dan wanita karir. Penelitian ini menerapkan teori Uses and Gratification dengan pendekatan kuantitatif. Populasi penelitian ini adalah mahasisiwi dan wanita karir. Pengumpulan data penelitian ini dilakukan dengan menyebarkan kuesioner kepada 100 mahasiswi dan wanita karir followers @Carmel_id. Data yang terkumpul diolah melalui SPSS 26. Penelitian ini menunjukkan bahwa ada pengaruh promosi online terhadap kepuasan informasi sebanyak 77,6%, sementara 22,4% dipengaruhi oleh faktor yang lain. Penelitian ini memberikan hasil jika promosi online meningkat maka kepuasan informasi juga akan meningkat.